Qualitative Study of Fine Arts Learning Management Innovation in Increasing Early Childhood Imagination - Nurlina Nurlina; Rasid; Halima; Herlina Permata Sari (Journal of Art and Creativity in Early Childhood Education, 2026)
This study aims to describe and analyze the innovation of art learning management in increasing early childhood imagination in Aisyiyah 1 Kendari Kindergarten. This study uses a qualitative approach. The research subjects consisted of the principal and three deliberately selected classroom teachers. Data collection techniques were carried out through observation, interviews, and documentation, then analyzed using the Miles and Huberman interactive model which included data reduction, data presentation, and conclusion drawn. The results of the study show that the management of fine arts learning is carried out through the stages of planning, organizing, implementing, and evaluating. Learning activities include drawing, coloring using watercolors, collages, and mosaics using natural materials and waste materials. Although the use of media is quite varied, the learning process still tends to be teacher-centered so that children imitate many of the examples given. Learning evaluation emphasizes more on the results of the work than on the child's creative process. The conclusion of the study shows that innovation in the management of fine arts learning is needed to provide a wider space for the development of children's imagination through more flexible and process-oriented learning.